Україна в концепії Єжи Гедройця на стрінках польських медіа - Комова, Марія (Видавництво Львівської політехніки, 2016)
Jerzy Giedroyc – the Polish journalist and editor of the Parisian magazine "Culture" did not expect to create the complete large-scale picture of the political life of Poland, but in his journalistic writings published in various Polish media with touches – well-aimed estimated comparisons, arguments, suggestions – he marked points of reference of the Polish domestic and foreign policy. At those points he builds measurement scale – perspective scale of the development of Poland. A key element in the concept of a new political thought of the Gedroyts is is the assessment of historical acquisition that was inherited by Poland and Ukraine, upgrading views on the painful pages of the past that brings together Ukrainian and Polish peoples in need of realistic and modern accents.
Keywords: мас-медіа; інформаційний простір; національна ідентичність